Al2O3 coated glass by aerosol deposition with excellent mechanical properties for mobile electronic displays - Yu, Hak Ki; Oh, Seungbae; Choi, Kyung Hwan; Jeon, Jiho; Dong, Xue; Lee, Sang Hoon; Choi, Jae Young; Akedo, Jun; Park, Jae Hyuk (Ceramics International, 2021)
Al2O3 thin film was deposited on Gorilla glass using an aerosol deposition method to improve the mechanical property of cover glass for mobile electronic device. The deposited Al2O3 film (approximately 1 μm thick) was a polycrystalline structure and showed a high light transmittance of approximately 90% in the visible light region. The CIE color space (L*a*b) measurement also showed a characteristic corresponding to the acceptable optical range of the cover glass. Further, it was confirmed that the bending strength improved by 10 %, as compared with bare Gorilla glass (from 6970 kgf/cm2 to 7704 kgf/cm2), and the Vickers hardness increased to approximately 1700–2000 HV, as compared with that of Gorilla glass (<700 HV). Owing to the improved mechanical properties, the Al2O3 thin film exhibited good anti-scratch properties and is expected to be applied to the cover glass of various display products.
Keywords: Aerosol deposition; Al2O3 coated glass; Coated glass; Cover glass; Electronic display; Mechanical; Mobile electronics; Property; Scratch resistant glass; Thin-films; Aerosol deposition; Al2O3 coated glass; Scratch resistant glass